P708 Post-COVID-19 and Quality of Life in Patients with Immune Mediated Inflammatory Diseases. (30th January 2023) - Schlosser, T; Krasselt, M; Elsing, L; Hecker, M; Holler, B; Hoffmeister, A
Abstract: Background: Pandemic situation of the novel coronavirus disease (COVID-19) represents a challenging condition with a plethora of aspects. Symptoms of patients with immune mediated inflammatory diseases (IMID) such as inflammatory bowel disease and different rheumatic diseases are not well described. Persistent symptoms following acute COVID-19 are quite frequent. Methods: IMID patients over the age of 18 years were prospectively asked for participation. Recruitment took place at our university outward centre between April and October 2022. Assessment was conducted as questionnaire-based study about the individual COVID-19 history since start of the pandemic in January 2020. Results: 156 patients filled in the documents. Large part of the participants had a diagnosis of inflammatory bowel disease (117 [75%] vs. 39 [25%] patients with rheumatic disease). Eightyone patients (51%) selfreported about a positive COVID-19 history. Diagnosis had usually been proven by PCR. In general, courses of infection were rather mild: Only two patients (2% of patients with reported COVID-19) were admitted to hospital due to COVID-19 with one of the two in need for intensive care. No symptoms of COVID-19 had been described by seven persons (9% of patients with reported COVID-19). Post-COVID-19 condition represents a not very well described continuum of persisting symptoms following acute course. WHO proposes a definition of at least one symptom, that persists three months from the onset of acute COVID-19. Twenty persons (25%) met this criterion; 19 patients (23%) were still suffering from post-COVID-19 at time of study participation. Quality of life (QOL) was globally assessed by a visual numeric scale (from 0 [=lowest QOL] to 100 [=highest QOL]). Mean/median of QOL reached 71.5/75 points in the cohort without post-COVID- 19 condition compared to 61.9/60 points in the post-COVID-19 cohort, respectively. One-sided t-test showed significant association of post-COVID-19 condition to lower QOL (p=.03). Conclusion: A notable fraction of IMID patients suffered from post-COVID-19 condition. This condition had negative impact towards quality of life.